Antara Desa dan Marga: Pemilihan Struktur pada Perilaku Elit Lokal di Kabupaten Lahat, Sumatera Selatan - Dedi Adhuri (Antropologi Indonesia, 2002)
In this article I discuss the impact of Village Law No.5, 1979 on the social actions of local elites. Using a case study of a traditional community (marga) located in Lahat, South Sumatera, I argue that Village Law No.5, 1979 did not marginalize tradition or the traditional community. At a practical or behavioral level, actors, in this case local elites used both tradition and Village Law as references for their actions. However, these two structures, tradition and Village Law were subject to selection. The selection was based on the actors understanding about particular context and the goal(s) of their actions. When tradition offered efficient means for achieving their goals, they selected tradition as a reference point for their behavior. In another context, when they saw that the Village Law offered more to suit their interest, they referred to it. It was also possible that, in a particular context, actors used and ignored the existence of some elements of both structures. In conclusion, I suggest that despite the fact that the application of the Village Law should have been understood to replace the traditional system of marga, people still used it as reference for their actions. Therefore, it would be misleading to say that Village Law has marginalized the traditional social organization.